Karakterisasi Biochar Pelepah Kelapa Sawit Hasil Pirolisis Berdasarkan Analisis Proksimat, pH, dan FTIR - Galuh Puja Kesuma; Siti Aisyah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Oil palm fronds (OPF) are the most abundant lignocellulosic biomass waste from oil palm plantations in Indonesia, yet remain underutilized. This study aims to characterize biochar produced from oil palm fronds through pyrolysis at 350–400°C for 4 hours under limited oxygen conditions. Characterization was conducted through proximate analysis (moisture content, ash content, volatile matter, and fixed carbon), pH measurement, and functional group analysis using Fourier Transform Infrared (FTIR) spectroscopy. This research employed a descriptive quantitative method with 2 replications. Proximate analysis results showed moisture content of 2.88%, ash content of 11.9%, volatile matter of 32.1%, and fixed carbon of 53.1%. The biochar pH value was 10.1, categorized as alkaline. FTIR analysis at UPT Integrated Laboratory, Universitas Negeri Malang identified 10 absorption peaks in the range of 447.57–2339.70 cm⁻¹, indicating functional groups characteristic of lignocellulosic-based biochar, including C–H, C–C, C–O, C=C, C=O, and aromatic ring structures. Comparison with SNI 06-3730-1995 standards shows that only the moisture content parameter meets the requirements. Despite this, the alkaline pH and detected functional groups suggest strong potential for OPF biochar application as a soil amendment, particularly for acid soils commonly found in Indonesian plantations.